Libyan Foreign Policy Under Institutional Division: Limits of Effectiveness and Possibilities for Recovery (Comprehensive Journal of Science, 2026)
This research aims to demonstrate the impact of institutional division in Libya on the effectiveness of Libyan foreign policy. It does so by analyzing the relationship between the fragmentation of internal decision-making centers and the diminished capacity to manage foreign affairs in a unified and effective manner. This topic is of paramount importance given the political and security transformations Libya has witnessed, which have directly impacted the performance of its institutions, particularly those involved in foreign policy decision-making and the implementation of diplomatic policy. The research is based on the fundamental premise that institutional division has contributed to the weakening of Libyan foreign policy through the multiplicity of authorities, divergent positions, and a decline in the ability to represent the state coherently in regional and international forums. The research employs a descriptive-analytical approach to examine the manifestations of this impact and its political and diplomatic dimensions, with a focus on the role of external interventions in exacerbating this weakness and narrowing the scope of action available to Libyan decision-makers. The research concluded that institutional division was not merely an internal crisis, but had become a major factor in disrupting and weakening the effectiveness of Libyan foreign policy. This made it difficult to utilize diplomatic tools in a way that served the nation's best interests. The research also concluded that unifying sovereign institutions is the most important step toward restoring some effectiveness to Libyan foreign policy, which necessitates working to strengthen national consensus and build a unified and stable foreign policy decision-making process.
Keywords: Institutional division, Libyan foreign policy, diplomatic effectiveness, foreign interventions, foreign policy decision-making.